Supply network design and the utilisation of rubber seed oil as biofuel and biochemicals - Ng, Wendy; Lam, H.; Yusup, S. (2012)
The supply network design and the utilization of rubber seed oil (RSO) in Malaysia are presented. Rubber plantation covers ~ 20% or 1.02 million ha of commercial plantation area in Malaysia. At average, 1 ha of land yields 150 kg of oil bearing seeds. The rubber seeds yields good amount of oil at 30-40 wt % of the seed. At 20% seeds utilization, 35 wt % oil extraction ratio and 96 wt % oil conversion rate, 10,310 ton/yr of biodiesel could be produced. This increases the country's energy security by developing another potential renewable energy source. RSO has good potential to meet the renewable energy share in Malaysia as well as the growing biodiesel market globally. After extracting oil from rubber seeds, the biomass or seeds left over could be used to feed cows, pigs and other livestock. These applications direct the utilization of rubber seeds to a zero-waste path. The supply network of the biomass was synthesized through mathematical programming. Centralised processing facilities are proposed and optimized biomass distribution network is presented. To elucidate the model, a simplified real case study is presented. This is an abstract of a paper presented at the CHISA 2012 - 20th International Congress of Chemical and Process Engineering and PRES 2012 - 15th Conference on Process Integration, Modelling and Optimisation for Energy Saving and Pollution Reduction (Prague, Czech Republic 8/25-29/2012).